A Legal Review of Roasting Actions by Comedians from the Perspective of Positive Law on Reputation Protection in Indonesia - Joshua Evandeo Irawan; Annabella Marcella Geraldine Kandou; Andrew Johnathan Setia; Sari Mandiana (Universitas Negeri Semarang, 2025)
This study examines the legal implications of roasting in stand-up comedy from the perspective of Indonesian positive law, particularly in relation to the protection of reputation, dignity, and honor. Roasting, as a comedic technique involving satirical criticism often directed at public figures, raises legal concerns when it potentially infringes upon the personal rights of those being criticized. This research employs a normative-dogmatic legal method using legislative and conceptual approaches to analyze the applicable legal framework, including the Criminal Code (KUHP), the Law on Information and Electronic Transactions (UU ITE), and the Personal Data Protection Law (UU PDP). The analysis is grounded in legal protection theory and the principle of legal utility, emphasizing that while freedom of expression constitutes a fundamental human right, it must be balanced against the rights to privacy and reputation. The findings indicate that defamation under Indonesian law constitutes a complaint-based offense, whereby legal proceedings may only be initiated upon a report by the injured party. Consequently, roasting conducted with the explicit consent of the subject, supported by a prior agreement regarding content and delivery, does not constitute an element of a criminal offense. This study proposes the use of written contracts between comedians and their subjects as a preventive legal mechanism to ensure legal certainty and minimize potential disputes. Ultimately, the study concludes that roasting, when appropriately regulated and based on mutual consent, can coexist with legal norms safeguarding individual dignity, thereby harmonizing freedom of expression with the right to reputation.